Persistence of Toxic Activity of Fermentation Extracts from Bacillus thuringiensis var. israelensis after More Than Three Decades of Storage - Galán Wong, Luis Jesús; Gamiño Hernández, Rossana; Fernández Chapa, David Daniel; García Díaz, Graciela; De la Garza Ramos, Myriam Angélica; Guajardo Barbosa, Claudio; Luna Olvera, Hugo Alberto (2017)
This study was carried out to determine the persistence of toxicity of fermentation extracts of Bacillus thuringiensis var. israelensis after more than three decades of storage. For this purpose, a population of Aedes aegypti was established. The mortality rate of 20 spore-crystal extracts purified using the acetone-lactose coprecipitation method was measured and evaluated by bioassays according to a modified WHO protocol. The extracts with the highest mortality rate were determined in triplicate by their LD50 and LD98. All extracts showed toxicity at the highest tested dose (1000 ppm) and some, such as strains 3260 and 3501, still killed larvae at doses as low as 0.01 ppm. These data are surprising because no study on the activity of B. thuringiensis toxic proteins after such a long storage time has been reported.